Clinical Profile and Outcomes of Central Microbial Keratitis in the Philippines - Ma. Dominga B. Padilla, MD; Ruben Lim Bon Siong, MD; George Michael N. Sosuan, MD (Philippine Journal of Ophthalmology)
Objective: Despite being a preventable and treatable condition, central microbial keratitis (CMK) and its complications remain to be a significant cause of vision loss in our country. This study presents the demographic profile, risk factors, etiologies, treatments, and outcomes of CMK in the Philippines.